RANCANG BANGUN SISTEM INFORMASI PENILAIAN KINERJA SUMBER DAYA MANUSIA KESEHATAN DI PUSKESMAS KALIRUNGKUT - Rohman, Falis; Sunarto, M.J Dewiyani; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Minister of Health of Indonesia has issued a decision in the context of performance assessment of health human resources in health centers. PHC Kalirungkut in this case has not been fully to assess the performance of health human resources in accordance with the Decree of the Minister of Health number 857 / Menkes / SK / IX / 2009 as was recommended . Performance appraisal is currently done by the health center is still in the process Kalirungkut manually. This can lead to errors such as human error , data loss , and data can be corrupted. To overcome these problems , then made a solution Design of HR information systems performance assessment Kalirungkut health in health centers . This application can perform data management , calculate the value of the performance , to reporting the performance of existing health human resources in health centers Kalirungkut . This application also can make the data more accurate calculation and timely , which will minimize the calculation error occurred. Based on the test results , it is known that the application can provide detailed information on the performance assessment of health human resources obtained from the collection of data effectively , so that the performance assessment can be done on time and not to be a delay granting any performance appraisal report has been completed.